Calculus (Derivatives)
posted by Mishaka .
Using the product rule, find the derivative of the following function:
(x^1/2 cscx sinx).

First off, csc * sin = 1
So, y = √x
However, if you insist on doing it the hard way
y = √x cscx sinx
y' = 1/2√x cscx sinx + √x(cscx sinx)'
= 1/2√x * 1 + √x(cscx ctnx * sinx + cscx cosx)
= 1/2√x + √x(ctnx + ctnx)
= 1/2√x
same answer
Respond to this Question
Similar Questions

Math, Calculus
Find the derivative of the function. y= xcosx  sinx What's the derivative? 
Calculus/Derivatives
In addition, can you walk me through how to get the derivatives for these 2 statements, too? 
calculus
express in sinx 1 1  +  cscx + cotx cscx  cotx and express in cosx 1 + cot x   sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!? 
PreCalculus
Find a numerical value of one trigonometric function of x if tanx/cotx  secx/cosx = 2/cscx a) cscx=1 b) sinx=1/2 c)cscx=1 d)sinx=1/2 
calculus
find the following derivatives: f(x) = (2x+5)/(x^23) f'(x)= (2)*(x^2 3)(2x+5)*2x/(x^23)^2 is that correct? 
calculus
Could someone check my reasoning? thanx Find the derivative of the function. sin(sin[sinx]) I need to use the chain rule to solve. So I take the derivative sin(sin[sinx) first. Then multiply that by the inside which is the derivative 
Applied Calculus
Find the first and second derivative of the function: x/(7x+10) Using quotient rule. This is part of my homework in the section named "Higher Order Derivatives". I am confused on getting the second derivative, as I found the first … 
Derivatives
Find the derivatives of: 1. H(x)= sin2xcos2x The answer given is 2cos4x. My question is, how in the world did they get that!? 
Calculus
What would an example of a logarithmic function that contains two trig functions within it where you would need to use chain rule and product rule to take derivative look like? 
Calculus
Just got through with derivatives, power rule, and chain rule. I am supposed to find the first and second derivatives of the function. y = 4x/√x+1 and y = cos^2(x) y' = [(x+1)^(1/2)(4)][(4x)(1/2(x+1)^(1/2))(1)] y' = [4(x+1)^(1/2)4x]/[2(x+1)^(1/2)(x+1)] …